(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the era of digital marketing, understanding consumer behaviour towards online advertisements is paramount for marketers to devise effective strategies. This study delves into the preferences of women consumers regarding online advertisements, recognizing the significance of this demographic in shaping market trends. Employing a mixed-methods approach, combining qualitative interviews and quantitative surveys, this research explores various factors influencing women’s perceptions and responses to online ads. Factors such as content relevance, visual appeal, interactivity, trustworthiness, and privacy concerns are analysed to uncover the underlying preferences of women consumers. Additionally, this study investigates the impact of demographic variables, including age, income, education, and online activity, on women’s attitudes towards online advertisements. Findings from this study offer valuable insights for marketers to tailor their online advertising strategies effectively, enhancing engagement and fostering positive relationships with women consumers in the digital realm.